Sustainable solution for microplastic removal: Sequential biodegradation and detoxification of polyethylene terephthalate microplastics by two natural microbial consortia - Minoo Giyahchi; Hamid Moghimi (Ecotoxicology and Environmental Safety)
Polyethylene terephthalate (PET) is a widely used plastic polymer, and its microplastics pose significant threats to ecosystems. One promising approach to addressing this issue is biodegradation using microbial consortia. This study implemented a two-stage biodegradation strategy using microbial consortia to degrade PET microplastics and detoxify their by-products. In the first stage, a bacterial/fungal consortium dominated by Ralstonia, Bradyrhizobium, Exophiala, and Vanrija achieved a 28 ± 2 % degradation efficiency over 60 days, converting PET into medium-chain alkanes (as confirmed by GC-MS analysis), with a maximum CO2 evolution rate of 722 ppm. Physical and chemical analyses, including Scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) analysis, and Fourier transform infrared (FTIR) spectroscopy, revealed structural destruction, mesopore formation, and ester bond breakage of the microplastics. Toxicity assessment of by-products showed a 40 % reduction in human endothelial cell viability, necessitating further detoxification. The second stage utilized a bacterial consortium dominated by Ochrobacterium and Achromobacter, which effectively reduced toxic by-products to 20 %. This study emphasizes the dual focus on efficient PET degradation and the safe decomposition of harmful by-products, showcasing the potential of sequential biodegradation strategies as sustainable solutions for microplastic pollution.